A REFUTATION FROM CAPITALISM TOWARD ENVIRONMENTALISM’S CRITICS RELATED ENVIRONMENTAL PROBLEM - Farucha, Riska Fara; Asnawi, Naupal (UI Scholars Hub, 2021)
From environmentalism’s perspective, there are four fundamental assumptions that make capitalism inconsistent with efforts to preserve the environment. First, unlimited growth in the capitalist system is contradicted with limited environmental conditions. Second, the basic principles of capitalism (individual freedom, self-interests, and free-market) are not compatible with efforts to preserve the environment. Third, capitalism has caused a